Penerapan Teknik Rainforcement Positif Untuk Meningkatkan Kedisiplinan Belajar Siswa (ILIN Institute Makassar, 2020)
This study aims to determine the level of student discipline as well as determine the effect of positif reinforcement techniques on increasing student discipline. Data collection techniques in this study used a questionnaire with a sample of 35 students from all grade X students with a population of 162 students in SMA Negeri 20 Pangkep. This type of research used in this study is an experimental study with one group pretest-posttest village design research design. The results showed that there was a difference between the test results before and after being given a positif reinforcement technique treatment of 0.660 at a significance of 0.879> 0.05. While the value of t arithmetic is smaller than t table (21,707 <1,697) at a significance level of 5%, it means that there is an influence on the application of the Positif Reinforcement technique to the discipline of student learning in SMA Negeri 20 Pangkep